2022
DOI: 10.1108/jaar-08-2021-0227
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the effect of temporary/permanent contracts on firm efficiency performance: evidence from South Korea

Abstract: PurposeBecause no international accounting policy exists to mandate human capital (HC) information must be reported on financial reports, the association between workforce HC and firm performance/efficiency is not well-established. South Korea is a rare example with high HC reporting quality, as well as relatively high national productivity. On the other hand, in some developed countries (such as the UK), HC reporting quality and productivity is low. Moreover, there is an increasing propensity to offer employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 114 publications
0
8
0
Order By: Relevance
“…To the best of our knowledge, no previous study integrates managerial effectiveness into the REM model. Fourth, as demonstrated in previous studies, relative and absolute efficiency are shown to be distinguishable (Baik et al ., 2013; Demerjian et al ., 2012, 2013; Frijns et al ., 2012; Lim and Mali, 2018a, 2022; Mali and Lim, 2019, 2020, 2022). This study extends the literature by demonstrating how relative efficiency and absolute efficiency can enhance the predictive validity of accounting models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, no previous study integrates managerial effectiveness into the REM model. Fourth, as demonstrated in previous studies, relative and absolute efficiency are shown to be distinguishable (Baik et al ., 2013; Demerjian et al ., 2012, 2013; Frijns et al ., 2012; Lim and Mali, 2018a, 2022; Mali and Lim, 2019, 2020, 2022). This study extends the literature by demonstrating how relative efficiency and absolute efficiency can enhance the predictive validity of accounting models.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that firms with higher levels of relative efficiency as a result of reducing unnecessary expenses demonstrate robust current and subsequent financial firm performance, compared to peers (Alam and Sickles, 1998; Baik et al ., 2013; Fairfield and Yohn, 2001; Greene and Segal, 2004; Soliman, 2008). Furthermore, managers that achieve maximum sales, using resources that are directly under their control are monitored by market participants, thus, enjoy economic benefits (Lim and Mali, 2018a, 2020, 2022; Mali and Lim, 2019, 2020, 2022). The efficiency literature therefore provides the basis to distinguish between two groups (1) Operationally Efficient Firms (OEF) with effective management that generate maximum sales from the optimal resource-cost mix of inputs, directly under their control.…”
Section: Introductionmentioning
confidence: 99%
“…Legislative oversight was a major contributing factor in the 1997 Financial Crisis (LaPorta, 1997 ; Emst, 1998 ). To enhance financial reporting transparency, South Korea is shown to be an early adopter of regulation policy (Choi et al, 2018; Lim & Mali, 2020 , 2022 , 2023 ; Mali & Lim, 2018 , 2019 , 2020 ). In 2023, South Korea is now the 10th largest economy based on GDP.…”
Section: Introductionmentioning
confidence: 99%
“…This growth in the number of temporary employees will impact the productivity and efficiency of an organization (Lim and Mali, 2022). Lim and Mali (2022) found that organizations with more temporary employees are less likely to be efficient and profitable. This may be due to the unpleasant experiences they encounter while working with permanent employees and the ignorant behaviour of the organization towards them (Clinton et al, 2020;Fisher and Connelly, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of temporary employment has been extensively studied in developed countries; however, there is scant research on it in a developing nation such as India, which had 1.3 million temporary employees in the organized sector in 2019 and is expected to grow by 10% by 2025 (Saigal, 2019). This growth in the number of temporary employees will impact the productivity and efficiency of an organization (Lim and Mali, 2022). Lim and Mali (2022) found that organizations with more temporary employees are less likely to be efficient and profitable.…”
Section: Introductionmentioning
confidence: 99%